Introduction to "Rome in Shakespeare’s Tragedies": How Shakespearean Material was Appropriated by Translators and Scholars during the Fascist Period - Tarantini, Angela Tizian; Griffiths, Christian (chronotopos – A Journal of Translation History, 2024)
What follows is a prefatory commentary and an English translation of the critical introduction to the text Roma nelle tragedie di Shakespeare (Rome in Shakespeare’s Tragedies) published in Italy in 1924. The book contains the translations of Julius Caesar and Coriolanus, both carried out by Ada Salvatore, and an introductory essay written by Giuseppe De Lorenzo. Our aim in translating the introductory essay by De Lorenzo is to raise awareness among non-Italian speaking scholars of how Shakespearian material was appropriated through translation by translators and intellectuals during the Fascist era.